2007
DOI: 10.1002/ijc.22749
|View full text |Cite
|
Sign up to set email alerts
|

Over‐expression of parathyroid hormone Type 1 receptor confers an aggressive phenotype in osteosarcoma

Abstract: Osteosarcoma is the most common primary bone malignancy in children and is associated with rapid bone growth. Parathyroid hormone-related peptide (PTHrP) signaling via parathyroid hormone Type 1 receptor (PTHR1) is important for skeletal development and is involved in bone metastases in other tumors. The aim of this study was to investigate the status of PTHrP/PTHR1 and its possible role in osteosarcoma. In a preliminary screening, a higher level of PTHR1 mRNA, but not PTHrP, was found in 4 osteosarcoma xenogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 51 publications
(81 reference statements)
3
57
0
Order By: Relevance
“…Tumor cells from patient-derived cell lines OS160CL and OS63CL were used to establish xenografts in mice as previously described according to a protocol approved by the Memorial Hospital Institutional Animal Care and Use Committee [37]. Xenografts were resected when the size was approximately 1.5 cm in diameter.…”
Section: Osteosarcoma Xenograftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor cells from patient-derived cell lines OS160CL and OS63CL were used to establish xenografts in mice as previously described according to a protocol approved by the Memorial Hospital Institutional Animal Care and Use Committee [37]. Xenografts were resected when the size was approximately 1.5 cm in diameter.…”
Section: Osteosarcoma Xenograftsmentioning
confidence: 99%
“…The housekeeping gene glyceraldehyde 3-phosphate dehydrogenase (GAPDH) was used as an endogenous control for template loading. Thermal cycling was performed with a 7500-fast real-time PCR system (Applied Biosystems 1 ) using a 2 9 TaqMan 1 Fast Universal PCR Master Mix provided by the manufacturer [37]. The relative quantity was calculated based on standard 2…”
Section: Construction Of Sage Librariesmentioning
confidence: 99%
“…In parallel to the occurrence of PTHrP, PTHR1 also seems to be present in other non-malignant and malignant tissues and is thought to mediate PTHrP-dependent effects on cell proliferation and differentiation. Most previous studies have detected the PTHR1 receptor on the mRNA level or via ligand-binding assays (7)(8)(9)(21)(22)(23)(24). Consequently, only limited information is currently available concerning the cellular and subcellular localisation of the PTHR1 receptor in human tissues.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Moreover, a recent report has shown that PTHR1 overexpression in a human osteosarcoma cell line resulted in its increased invasive capacity, associated with upregulation of TGF-␤1. 28 Also of interest in the present context, in both human embryonic kidney cells HEK-293 and osteoblasts, stimulation of PTHR1 may lead to EGFR transactivation. 29,30 Collectively, these findings suggest that PTHrP might interact with TGF-␤ and/or EGFR to modulate EMT.…”
mentioning
confidence: 97%